Research on High-Precision Calculation Method for Permanent Magnet Synchronous Motor Efficiency in Electric Vehicles Across Full Load-Speed Range - Yukuan Li; Huichao Zhao; Sibo Wang; Wan Huang; Yao Wang; Bo Gao; Wei Pang; Tianxu Zhao; Yuan Cheng (Energies, 2025)
In order to accurately calculate the efficiency of electric vehicle drive motors in the full speed range during the design phase, this paper proposes a comprehensive motor loss fast calculation method. Firstly, a high-fidelity joint simulation model of control and design was established to simulate the real excitation sources in actual operation. Secondly, detailed modeling was conducted for each loss. Regarding iron loss, this paper considers the effects of PWM harmonics, as well as cutting, welding, and other processes, on the loss based on finite element calculations. This paper proposes a semi-analytical AC copper loss calculation method, which superimposes the effective section and end winding separately. A fast improvement simulation method is proposed for the eddy current loss of permanent magnets, which equivalently combines 2D finite element and 3D finite element, while considering factors such as segmentation. Finally, a loss separation scheme was designed and experimentally verified for each loss and motor efficiency, proving that the efficiency calculation error of most operating points was less than 1.5%.